Trends in The Development of Articulate Storyline Media in Science Learning in Elementary Schools (2020-2025) - Fitriyani, Fitriyani; Handayani, Langlang; Subali, Bambang; Widiarti, Nuni (Journal of Educational Sciences, 2026)
Technological developments have driven innovation in science education. One innovation in science education is the development of Articulate Storyline media. This study aims to analyze the novelty and findings of trends in the development of Articulate Storyline media in science education in elementary schools for the period 2020-2025. This study uses a systematic literature review method. Articles were searched through Publish or Perish from Google Scholar using the keywords “development” and “Articulate Storyline”. The search yielded 28 articles from a total of 500 articles that matched the context of the title and abstract to be analyzed based on novelty and findings, thus revealing research opportunities. The novelty analysis results showed that there was integration of media with Problem Based Learning, Discovery Learning, Contextual Teaching and Learning, Culturally Responsive Teaching, Critical Thinking Skills, 21st Century Competencies, and STEM. The findings analysis results showed that there was effectiveness in learning outcomes, interest, concept understanding, science literacy, and critical thinking skills of students. In conclusion, this trend opens up opportunities for further research in developing Articulate Storyline media with more innovative integration to improve the learning needs of elementary school students.